Parents’ Perceptions of Suicide and Requests for Increased Awareness in Prevention of Children’s Suicidal Behavior - Svetlana V. Knizhnikova (Интеграция образования)
Introduction. The issue of suicidal behavior among minors highlights the need to explore preventive measures within the family. Optimizing family-based suicide prevention for children necessitates the assessment of parental awareness regarding the phenomenon of suicidal behavior and the potential strategies for prevention. This serves as the primary objective of the study.